ISCHEMIC STROKE: PATHOPHYSIOLOGY, DIAGNOSIS, AND MODERN THERAPEUTIC APPROACHES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
Ischemic stroke is one of the leading causes of mortality and long-term disability worldwide. It occurs due to an abrupt interruption of cerebral blood flow, resulting in neuronal injury and brain infarction. Rapid diagnosis and timely reperfusion therapy are critical for improving outcomes. This article reviews the pathophysiology, diagnostic strategies, acute management, and long-term prognosis of ischemic stroke. Advances in thrombolysis and mechanical thrombectomy have significantly improved survival rates and neurological recovery. However, early recognition and prevention remain essential in reducing disease burden.